The complete mitochondrial genome sequence of Cirrhinus mrigala (♀) × Labeo rohita (♂). (3rd May 2016) - Wu, Ping; Chen, Dunxue; Guo, Xinhong; Chu, Wuying
Abstract: We cloned and sequenced the complete mitochondrial DNA (mtDNA) of Cirrhinus mrigala (♀) ×  Labeo rohita (♂) by PCR-based method. The total of the mtDNA was 16, 595 bp. It consisted of 13 protein-coding genes, 22 tRNAs, 2 rRNA genes, and one putative control region (D-loop region). The overall base composition on strand was as follows A: 32.09%, G: 15.51%, C: 27.95%, T: 24.45%, and the A + T content 56.54%. All the protein-coding genes initiated by typical ATG codon, and ten genes ended with the complete stop codon TAA or TAG, while COII2, ND4 and Cytb genes terminated with GCC, TAT and GCT. The control region contains a thiolases active site, EGF-like domain signature and two anaphylatoxin domain signature. This mitogenome sequence data would play an important role in population genetics and phylogenetics of the hybrid fish in the Cyprinidae family.